Proposta de um modelo para a análise das relações entre a capacidade de gestão e a capacidade de inovação de micro e pequenas empresas do sul do Brasil - Carvalho, Gustavo Dambiski Gomes de (2021)
Micro and small companies (MSEs) contribute strongly to the Brazilian economy and seek to remain competitive, especially by means of innovation. In this setting, this research aims to propose a statistical model for the analysis of the relationships between management capabilities and innovation capabilities of micro and small companies. In order to achieve it, in addition to three bibliometric reviews on management and innovation in MSEs, 11 models were proposed and analyzed using the statistical technique of partial least squares - structural equation modeling (PLS-SEM). Besides, in terms of originality, advanced analyses as second order constructs and effects of control variables were applied based on a sample of 5,633 Brazilian MSEs participating in the Local Innovation Agents Program (ALI Program) in the states of Paraná, Santa Catarina and Rio Grande do Sul. Among the main findings, the dimensions of the Excellence Management Model (MEG) for MSEs (Leadership; Strategy, Customers; Society; People; Information-Knowledge and Processes) were validated as firstorder constructs, in addition to being able to be aggregated in a second-order construct denominated Enabling factor. However, the absence of differentiation of these dimensions in terms of Technical (Hard) and Social (Soft) factors as second-order constructs was verified statistically. In turn, to measure MSEs’ innovation capabilities, the new innovation subtypes of the fourth and last version of the Oslo Manual were used as a theoretical basis, where the individual questions in the Innovation Radar questionnaire were reorganized and statistically validated in this new classification, namely: Product Innovation; Production Innovation; Distribution Innovation; Innovation in Information and Communication Technology (ICT); Marketing Innovation; and Management Innovation. Particularly on the relationship between management capabilities and innovation capabilities, the results revealed that all management dimensions positively and significantly influence at least one innovation dimension, where Information-Knowledge and Customers were the outstanding management dimensions. In addition, the inclusion of Size and Sector (manufacturing) control variables revealed significant differences in the management capabilities of micro and small companies, where small companies had higher levels than micro, as well as differences between sectors, where industrial companies presented higher levels in Society and Processes while service companies in Leadership and People. Particularly on the effects of the controlling variables on the relationship between management capabilities and innovation capabilities, partial control and suppression effects were identified, especially of Sector on Processes and Society management dimensions, where the effect of Processes on innovation dimensions was reduced in most relationships. On the other hand, the results showed that, in general, the effects of MSEs management capabilities on innovation capabilities were maintained regardless of Size or Sector. In addition to the theoretical contributions of these findings, as an outstanding practical contribution, SME owners and managers may focus on the management dimensions that had the greatest positive influence on each innovation dimension that they seek to improve. Thus, it is expected that this work will contribute to increase the innovation capabilities and, consequently, the competitiveness of Brazilian MSEs.